2017
DOI: 10.1097/mpa.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Direct Pancreatic Function Testing in Children

Abstract: Endoscopic pancreatic function testing can be used in the evaluation of EPI in children. Normative data suggest that pancreatic enzyme activities mature with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The limitations of the study are all patients did not undergo EUS assessment. The performance of FE‐1, although an ideal noninvasive marker for pancreatic exocrine insufficiency, is not optimum in mild insufficiency, where invasive pancreatic stimulation test would have been a good alternative . We could not perform genetic testing for the pancreatitis causing mutations and IgG4 levels; thus, etiology in many patients remained unknown (idiopathic).…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the study are all patients did not undergo EUS assessment. The performance of FE‐1, although an ideal noninvasive marker for pancreatic exocrine insufficiency, is not optimum in mild insufficiency, where invasive pancreatic stimulation test would have been a good alternative . We could not perform genetic testing for the pancreatitis causing mutations and IgG4 levels; thus, etiology in many patients remained unknown (idiopathic).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016 a larger study with 508 ePFTs in children reported peak enzyme activities at 5 min that was then followed by a decrease activity over time ( 144 ). Additionally, they found discordance between ePFT and FE-1 testing in 165 children ( 144 ).…”
Section: Direct (Stimulatory) Exocrine Function Testsmentioning
confidence: 99%
“…Schibli et al also noted that shortening the duration of sampling to 20 minutes from 60 minutes missed the maximal rate of enzyme output in many of the cases. However, the duration of sampling is not a fundamental difference between the two tests, and several studies of ePFT in both children and adults, described in the next section, demonstrate that the peak enzyme activities and bicarbonate level were achieved within 20 minutes of starting the collections and as early as 5 minutes in the enzyme activity calculations, when there was more rapid stimulation with secretin alone (24,(29)(30)(31)(32)(33). The study above highlights that the field is still in need of studies to help develop the optimal method for ePFT in children.…”
Section: Controversy In the Pediatric Literature Between The Dreiling...mentioning
confidence: 99%
“…(29) The collection after secretin and CCK provided similar enzyme activities at 5 and 10 minutes with significant decline at 15 minutes No statistically significant difference between secretin and CCK group Pfefferkorn et al (36) CCK can replace secretin if there is a secretin shortage; however, in case of CCK, the collection is recommended until 15 minutes Wali et al (37) Using 4 specimens after secretin administration, poor concordance between ePFT and fecal elastase in 70 children. Alfraro Cruz et al (30) From >500 ePFTs, authors recommended use of >1 specimen collection in ePFT. A subset of 165 children had both fecal elastase and ePFT results.…”
Section: Safety Of Endoscopic Pancreatic Function Testingmentioning
confidence: 99%